Linear/Nonlinear Dynamic Analysis and Prediction of Failure Mechanism of Irgandi Bridge - Sakcalı, Gökhan Barış; Gönül, Alper; Bağbancı, Muhammed Bilal; Yüksel, İsa (Periodica Polytechnica Civil Engineering, 2022)
The goal of this study is to investigate the behavior and failure mechanism of historical Irgandi Bridge located in Bursa City under earthquake loads by using linear and nonlinear dynamic analysis. Dynamic characteristics of the bridge is investigated by using in-situ Operational Modal Analysis (OMA) tests. The finite element model is updated according to the OMA tests. Three different artificial earthquake records from weak to very strong are applied to the model for understanding the damage zones and the failure mechanism of the historical bridge. The results show that the bridge does not reach the failure mechanism under weak earthquakes for nonlinear dynamic analysis. However, under strong earthquake even if damage zones are occurred and the stiffness of the bridge is decreased, there is no failure mechanism observed according to the nonlinear dynamic analyses. Under very strong earthquake loads the bridge reaches the failure mechanism according to the nonlinear dynamic analysis. As the earthquake level increases, the difference between linear and nonlinear dynamic analysis results increases due to structural damages. In addition, considering the soil-structure interactions, it is concluded that the dynamic characteristics could be reflected more accurately.